Nanomedicine: A Promising Way to Manage Alzheimer’s Disease - Khan, Nazeer Hussain; Mir, Maria; Ngowi, Ebenezeri Erasto; Zafar, Ujala; Khakwani, Muhammad Mahtab Aslam Khan; Khattak, Saadullah; Zhai, Yuan-Kun; Jiang, En-She; Zheng, Meng; Duan, Shao-Feng; Wei, Jian-She; Wu, Dong-Dong; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Alzheimer’s disease (AD) is a devastating disease of aging population characterized by the progressive and slow brain decay due to the formation of extracellular plaques in the hippocampus. AD cells encompass tangles of twisted strands of aggregated microtubule binding proteins surrounded by plaques. Delivering corresponding drugs in the brain to deal with these clinical pathologies, we face a naturally built strong, protective barrier between circulating blood and brain cells called blood brain barrier (BBB). Nanomedicines provide state-of-the-art alternative approaches to overcome the challenges in drug transport across the BBB. The current review presents the advances in the roles of nanomedicines in both the diagnosis and treatment of AD. We intend to provide an overview of how nanotechnology has revolutionized the approaches used to manage AD and highlight the current key bottlenecks and future prospective in this field. Furthermore, the emerging nanomedicines for managing brain diseases like AD could promote the blooming growth of research and their clinical availability.